Mountaineering and altitude sickness: a study of AMS prevalence among climbers of Mount Kinabalu, Malaysia - Abdullah, Muhamad Aliff; Yaakob, Sam Shor Nahar; Ismail, Mohd Hafizal; Samsudin, Shamsulariffin; Farizan, Noor Hamzani (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2023)
Introduction: Adventure tourism has become one of Malaysia’s most attractive tourism demands, and mountain climbing is rapidly becoming a popular recreational sport. Exploring mountain adventures offers a dynamic experience, preserving this fascinating activity, yet the climbers are exposed to the risk of altitude sickness, such as Acute Mountain Sickness (AMS). This study aimed to evaluate the prevalence of AMS and investigate the effects of high-altitude sickness on the climber profile associated with climbing at Mount Kinabalu, Malaysia. Methods:. The Lake Louise acute mountain sickness LLS score questionnaire collected 95 climber’s data at four different altitudes. SPO2 and Pulse rate was (PR) measured using a finger pulse oximeter. In a cohort study, AMS was measured on day one at 1866m (1st station), 3622m (2nd station), and day two at 3810m (3rd station), and 4095m (4th station). Results: At the altitude of 1866 (Timpohon Gate), the prevalence of AMS was 0%, 30% at 3622m (Laban Rata), 34.7% at 3810m (Sayat-Sayat), and 37.9% at 4095m (Low’s Peak). The overall prevalence of AMS was 37.9% and the majority of AMS cases were moderate in severity and the LLS score is significant with Pulse Rate and peripheral capillary oxygen saturation (SPO2). Conclusion: Concisely, this finding has triggered a need for consideration from multi agencies to enhance mountaineering guidance, especially for beginners or inexperienced hikers, for a suitable package for climbing attempts to reduce the incidence of AMS among Mount Kinabalu climbers.